The life and work of Professor Adrianus Van Selms - Van Rooy, H. F. (Journal for semitics, 2013)
Journal for Semitics has been priviledged to publish the annual Van Selms Memorial Lecture since 2010. The lecture is the keynote address at the annual congress of the South African Society of Near Eastern Studies (SASNES). In 2012, the lecture was read by H.F. van Rooy, and is published in this volume. Professor van Rooy also penned this brief biographical essay on the life and work of Adrianus van Selms.